Akal Budi sebagai Penopang Kehidupan Manusia: Refleksi atas Pemikiran Fahruddin Faiz - Ulumudin, Ihya; Asbari, Masduki; Aulia, Khusnul (Journal of Information Systems and Management (JISMA), 2025)
This study aims to examine how reason, as the highest gift to humans, plays a role in maintaining the direction and values of life amid moral, social, and spiritual challenges in the modern era. This research uses a qualitative-descriptive method by conducting observations and literature studies. The main source comes from the YouTube video Endgame #110 entitled “Dr. Fahruddin Faiz: Reason is Not to be Wasted,” which conveys a philosophical message about the importance of honoring reason as a divine mandate. The results of the study show that reason plays a central role in character building, spiritual development, and strengthening critical thinking. This study stems from the author's reflection on the urgency of Islamic values and philosophy education in shaping wise and civilized social awareness.